Karakteristik Kerupuk Ikan Baung Dengan Jenis Pati Berbeda - Gunawan, Hendri; Handayani, Lia; Maulidya, Rulita (Jurnal TILAPIA, 2025)
This study aimed to evaluate the effect of different starch types on the physical, chemical, and organoleptic characteristics of baung fish (Hemibagrus nemurus) crackers. Three types of starch were used in the cracker formulations: tapioca starch (P1), sago starch (P2), and cornstarch (P3). The analyses included expansion ratio, organoleptic evaluation (taste, aroma, color, and texture), and proximate composition (moisture, ash, fat, protein, and carbohydrate content). Organoleptic data were analyzed using the Kruskal-Wallis test, followed by the Mann-Whitney test for significant differences, and Bayes analysis to determine the best treatment. The results showed that crackers made with tapioca starch (P1) exhibited the highest expansion ratio. Organoleptic testing indicated that P1 was most preferred in terms of taste (8.83±0.461) and texture (8.50±0.820), while the best aroma was recorded for P2 (7.90±1.269), and the most preferred color was found in P3 (7.50±1.737). Proximate analysis revealed that P1 had the highest moisture (9.35%), fat (2.52%), and protein (11.23%) contents. The highest ash content was observed in P3 (5.72%), while P2 showed the highest carbohydrate content (77.72%).